Actio Popularis in International Accountability: A Case Research of the UAE - Simanjuntak, Calvin Paulus Marcelito (Faculty of Law Universitas Lampung, 2025)
Nationality deprivation has become a tool of political repression, undermining fundamental human rights and rendering individuals stateless. In the United Arab Emirates, the government increasingly uses nationality deprivation to silence political dissidents, raising concerns about compliance with international legal standards. This research examines the UAE’s nationality deprivation policies in light of international human rights law and explores the potential of actio popularis as a legal mechanism for holding states accountable. Using a normative legal analysis, the paper evaluates the UAE’s practices against key international treaties, including the Arab Charter on Human Rights and the 1961 Convention on the Reduction of Statelessness. It also assesses the relevance of actio popularis, erga omnes, and erga omnes partes principles in enabling states to challenge human rights violations affecting collective international interests. Drawing on recent case law, such as The Gambia v. Myanmar, this research explores how states may invoke these doctrines before international courts. The findings indicate that the UAE’s nationality deprivation practices violate key principles of proportionality and non-arbitrariness under international law, contributing to statelessness and severe human rights abuses. This research underscores the evolving role of actio popularis in international accountability and advocates for its broader application in nationality deprivation cases. Strengthening international safeguards against arbitrary nationality deprivation is essential for ensuring legal protection and preventing the misuse of citizenship laws as a tool of repression.